Irrigaciones, tierra y sociedad en la costa peruana: 1890-1930 - Espinoza Claudio, César (2022)
In this essay, we study the impact of hydraulic technology in Piura’s agriculture in the context of the government of Augusto B. Leguía. The first part systematizes relevant ideas on irrigation and civilization, coastal agriculture, and the internal market. In the second part, we present a balance of the studies carried out between 1870-1940, with the introduction of irrigation technologies in the 20th century. In this sense, we review Leguía’s agrarian policy and Charles Sutton’s ideas to achieve agricultural modernization of Piura using irrigation technology.